1987
DOI: 10.1149/1.2100651
|View full text |Cite
|
Sign up to set email alerts
|

X‐Ray, Photoluminescence, and SIMS Characterization of InGaAs / InP Grown by Vapor Phase Epitaxy

Abstract: X‐ray double crystal diffractometry (DCD), low temperature photoluminescence (PL), and secondary ion mass spectrometry (SIMS) have been used to characterize single epitaxial layers grown by hydride‐, chloride‐, and levitation‐vapor phase epitaxy (VPE). Coherent hydride layers exhibited both bound exciton and C related donor‐acceptor peaks, and the deduced bandgaps and alloy compositions were found to agree with published values. For coherent hydride‐VPE layers shifts of no more than 1 meV in the PL spectra for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…For incoherent epitaxy, an additional term proportional to the in-plane mismatch must be added to the right side of Eq. [2]. However, for the presently studied wafers this correction is either zero or is quite small, as judged from the measured magnitude of (ha~a), the thickness of the mismatched layer, and the full width at half maximum (FWHM) of the Bragg peak.…”
Section: Calculation Of Stoichiometrymentioning
confidence: 91%
See 1 more Smart Citation
“…For incoherent epitaxy, an additional term proportional to the in-plane mismatch must be added to the right side of Eq. [2]. However, for the presently studied wafers this correction is either zero or is quite small, as judged from the measured magnitude of (ha~a), the thickness of the mismatched layer, and the full width at half maximum (FWHM) of the Bragg peak.…”
Section: Calculation Of Stoichiometrymentioning
confidence: 91%
“…(We defer a discussion on how to obtain the mismatch from rocking curves and how to obtain the bandgap from photoluminescence spectra to the next section). Equation [2] for the lattice mismatch and Eq. [4] for the bandgap with the corrections given in Eq.…”
Section: Hydride Vpementioning
confidence: 99%
“…Detectable parallel mismatch has only been reported for crystals where the perpendicular mismatch is greater than +0.2%. Macrander & Swaminathan (1987) have noted that an exaggerated broadening of the 004 rocking-curve peaks of both the epitaxic layers and substrate signals the onset of incoherent epitaxic crystal growth. All the samples used for this study showed very narrow rocking curves.…”
Section: ( a ) Poisson " S Correctionmentioning
confidence: 99%